Studies on coliform organisms in Şavak cheese - O. Cenap Tekinşen; Bahri Patır; Mehmet Alkan (Eurasian Journal of Veterinary Sciences)
The occurence of coliform group microorganism species in şavak cheese were investigated in 45 samples. All of the samp!es contained coliform group microorganisms. The most occuring species in the samples were Aerobacter aerogenes 1 (75. 6 %), Escherichia coli I (70.1 %), Escherichia freundii 1 (48.9 %), Escherichia coli II (22.2 %), Aerobacter aerogenes II (13.3 %) and Escherichia freundii II (6. 7 %). Total 398 strains iso/ated consisted of 157 Escherichia coli 1 (39.5 %), 129 Aerobacter aerogenes 1 (32.4 %) and 54 Escherichia freundii I (13. 6 %). lt is concluded that şavak che es e consumed in Elaztğ area is produced under unhygienic conditions and may represents a potential hazard for public health.